2019
DOI: 10.1212/wnl.0000000000007235
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular adverse events associated with anti-PD-1 monoclonal antibodies

Abstract: Neuromuscular adverse events following cancer treatment with anti-programmed cell death protein 1 (PD-1) monoclonal antibodies are relatively rare, yet potentially fatal. We performed a systematic review to characterize the clinical presentation, diagnostic workup, and management of neuromuscular disorders (NMDs) in patients treated with nivolumab or pembrolizumab monotherapy or concurrent with other immunologic agents, such as ipilimumab. Sixty-one publications on 85 patients (mean age 66.9 years [range 34–86… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
115
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 74 publications
(69 reference statements)
4
115
2
Order By: Relevance
“…In a recent systematic review of 86 patients with metastatic melanoma (n = 51) or NSCLC (n = 15) treated with nivolumab or pembrolizumab, whether or not in combination with ipilimumab, 20 patients (23%) were diagnosed with demyelinating polyradiculoneuropathy . Patients commonly present with acute or subacute sensory motor symptoms and cranial nerve involvement with bulbar symptoms and dyspnea. Chronic evolution has been reported rarely eventually following an initial acute presentation .…”
Section: Clinical Syndromes and Presentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review of 86 patients with metastatic melanoma (n = 51) or NSCLC (n = 15) treated with nivolumab or pembrolizumab, whether or not in combination with ipilimumab, 20 patients (23%) were diagnosed with demyelinating polyradiculoneuropathy . Patients commonly present with acute or subacute sensory motor symptoms and cranial nerve involvement with bulbar symptoms and dyspnea. Chronic evolution has been reported rarely eventually following an initial acute presentation .…”
Section: Clinical Syndromes and Presentationsmentioning
confidence: 99%
“…Patients commonly present with acute or subacute sensory motor symptoms and cranial nerve involvement with bulbar symptoms and dyspnea. Chronic evolution has been reported rarely eventually following an initial acute presentation . Cerebrospinal fluid (CSF) analysis commonly shows albumino‐cytologic dissociation, possibly associated with mild lymphocytic pleocytosis (10‐15 cells/mm 3 ) .…”
Section: Clinical Syndromes and Presentationsmentioning
confidence: 99%
“…However, these reports have generally been limited to single malignancies (melanoma) and/or ICI class (anti–PD‐1 antibodies) . Other studies have reported clinical presentation of MG among patients treated with either nivolumab or ipilimumab monotherapy utilizing pharmaceutical company postmarketing surveillance databases . Because irAE‐N may present atypically with overlapping neurological manifestations and cancer, mortality and quality of life outcomes of currently recommended treatments are unknown; comprehensive phenotypic characterization and additional real‐world outcome data with longitudinal follow‐up are needed.…”
mentioning
confidence: 99%
“…However, multiple factors may contribute to respiratory deterioration, especially severe diaphragm involvement . The latest systematic review of neuromuscular adverse events associated with ICIs revealed that respiratory involvement is frequent (43%), and mortality is high . We describe here a patient with an irAE with persistent damage to the diaphragm muscle that was proven by electrophysiological and ultrasound (US) examination.…”
Section: Introductionmentioning
confidence: 95%
“…2,3 The latest systematic review of neuromuscular adverse events associated with ICIs revealed that respiratory involvement is frequent (43%), and mortality is high. 4 We describe here a patient with an irAE with persistent damage to the diaphragm muscle that was proven by electrophysiological and ultrasound (US) examination. After treatment with pulsed methylprednisolone injection (1 g for 3 days) and intravenous immunoglobulin (0.4 g/kg for 5 days) with subsequent oral corticosteroids (60 mg daily), the limb muscle weakness recovered but respiratory function did not.…”
Section: Introductionmentioning
confidence: 96%